Conventional Type 1 Dendritic Cells in Intestinal Immune Homeostasis - Sasaki, Izumi; Kato, Takashi; Hemmi, Hiroaki; Fukuda-Ohta, Yuri; Wakaki-Nishiyama, Naoko; Yamamoto, Asumi; Kaisho, Tsuneyasu (Frontiers in Immunology, 2022)
Dendritic cells (DC) play critical roles in linking innate and adaptive immunity. DC are heterogenous and there are subsets with various distinct functions. One DC subset, conventional type 1 DC (cDC1), can be defined by expression of CD8α/CD103 in mice and CD141 in humans, or by expression of a chemokine receptor, XCR1, which is a conserved marker in both mice and human. cDC1 are characterized by high ability to ingest dying cells and to cross-present antigens for generating cytotoxic CD8 T cell responses. Through these activities, cDC1 play crucial roles in immune responses against infectious pathogens or tumors. Meanwhile, cDC1 involvement in homeostatic situations is not fully understood. Analyses by using mutant mice, in which cDC1 are ablated in vivo, revealed that cDC1 are critical for maintaining intestinal immune homeostasis. Here, we review the homeostatic roles of cDC1, focusing upon intestinal immunity.